Dynamically Controlled In Situ Cascade Amplification Modulating Receptor Spatial Distribution and Cell Phenotype - Ruxiang Li; Sujun Jiang; Ziyu Zhu; Xiongwei Chen; Zihua Wang; Li‐Li Li (Advanced Healthcare Materials, 2026)
ABSTRACT Ligand‐receptor interactions play a crucial role in disease therapy. However, enhancing ligand‐receptor selectivity and precisely controlling subsequent cellular behavior remain significant challenges. In this study, we developed a receptor‐mediated cascade amplification strategy via glycopeptides (GPs) to regulate the dynamic self‐assembly of artificial ligands, enhancing ligand‐receptor selectivity. By designing the assembly sequences, we control the antagonistic relationship between dynamic nanostructures and receptor‐mediated internalization. Our findings show that in fast cascade amplification, rapid fiber network formation inhibits internalization, while in slow amplification, receptor aggregation enhances internalization, promoting cellular uptake. This precise regulation further impacts the spatial distribution and function of receptor, ultimately controlling cellular phenotypes. Based on real‐world needs, we applied the cascade amplification strategy to enhance the efficacy of PD‐L1 tumor immunotherapy. These findings provide new insights into the regulation of ligand‐receptor selectivity and receptor activity, offering promising potential for targeted enhancement and precise intervention of cellular activities.